الاختلاطات الوالدية للولادة المهبلية (خلال الطور الثالث والرابع للمخاض) - الدالي, عصام; عبد الرحمن, أحمد; علي, رفيف محمود (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في قسم التوليد وأمراض النساء- مشفى الأسد الجامعي- اللاذقية وامتدت من تاريخ 01/01/2003 حتى 01/06/2004 وتضمنت الدراسة المواخض في تمام الحمل وليس في سوابقهن قيصرية وكان عددهن 2300 ماخض, وجاء ت نتائج الدراسة على الشكل التالي: - حدثت الاختلاطات الوالدية عند 430 ماخض وشكلت نسبة 19.22% من مجمل الولادات. - حدثت الاختلاطات عند الولودات بنسبة أعلى من الخروسات (56.5% مقابل 43.5%). - تمثلت الاختلاطات الوالدية بما يلي : - تمزقات المسير التناسلي 16.78% . - العطالة الرحمية 1.69 % . - انحباس المشيمة 0.71% . - صمة أمنيوسية 0.043% . - أ كثر الاختلاطات مشاهدة عند الخروسات هو تمزق عنق الرحم 5.52% . - أكثر الاختلاطات مشاهدة عند الولودات تمزق العجان درجة (I) 14.23% . وكانت أهم العوامل المؤهبة لحدوث الاختلاطات : - المجيئات المعيبة . - عدم التناسب الحوضي الجنيني . - تحريض المخاض بالأوكسيتوسين . - الحمل المتعدد . - سن الحامل >35عاما". The study was carried out in the obstetrics and gynecology department at AL ASSAD university hospital in Lattakia at a time between 01/01/2003 and 01/06/2004. The study included the pregnants in labor who were between (38-40) weeks considerably to LMPand who had no previous cesarean section. The study included 2300 patients and the results are : -The maternal complications were noted in 430 patients (19.22%). -The higher incidence of the complications was in the multiparous women more than in nulliparous women who are having thrie first pregnancy (56.5% to 43.5%) . -The maternal complications were : - genital tract lacerations (16.78%). - uterine atony (1.69%) . - manual removal of the placenta (0.71%) . -amniotic emboly (0.043%) . -The complication which was the highest in the nulliparous women was the cervical laceration) 5.52% ). -The following factors are considered as predisposed factors for the complications: - abnormal presentations . - fetopelvic disproportion. - using of oxytocin. - multifetal pregnancy. - pregnant aged > 35 years.